2020
DOI: 10.3390/soc10040099
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Applied Behaviour Analysis Practitioners in Australia: Education, Training, and Barriers to Professional Practice

Abstract: In Australia, the prevalence of autism has increased over the past decade. This has resulted in increased demand for safe and effective interventions and supports. Many evidence-based interventions for individuals with autism have been derived from the scientific discipline of Applied Behaviour Analysis (ABA). However, the professional practice of ABA is not yet formally regulated in Australia, and there are no national practice standards or qualification requirements for practitioners providing ABA-based inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Given the recent establishment of two verified university course sequences in Australia, it is anticipated that the demand for supervision will continue to grow. The current study extends the findings of Leif et al ( 2020 ), who found that the most common barriers ABA practitioners in Australia face are access to training, supervision, and professional development opportunities. In the current study, specific barriers to delivering and accessing supervision in Australia were identified, as well as potential solutions to barriers.…”
Section: Discussionsupporting
confidence: 87%
“…Given the recent establishment of two verified university course sequences in Australia, it is anticipated that the demand for supervision will continue to grow. The current study extends the findings of Leif et al ( 2020 ), who found that the most common barriers ABA practitioners in Australia face are access to training, supervision, and professional development opportunities. In the current study, specific barriers to delivering and accessing supervision in Australia were identified, as well as potential solutions to barriers.…”
Section: Discussionsupporting
confidence: 87%